ANALISIS POTENSI KEBANGKRUTAN DENGAN METODE SPRINGATE PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDFATAR DI BURSA EFEK INDONESIA - Vera Anitra; Nur Laili Widyawti (Jurnal Ekonomi dan Manajemen, 2018)
The potential risk of bankruptcy is always attached to every business including the property and real estate industries. The purpose of the study is to identify potential bankruptcy on property and real estate companies listed on Indonesia Stock Exchange by Springate method. Using three samples with purposive sampling technique, data collection technique using secondary data. Data analysis from this study using Springate method look at from the company's financial statements. The results indicate company X bankruptcy, due to a decrease in the of working capital to total assets. The company Y experience conditions grea area in 2016 which means in the company in the conditions prone the bankruptcy, because of the produce a profit. Expected company can manage current liabilities well so that the company out of the conditions gre are. PT. Lippo Karawaci Tbk (LPCK) get assessment criteria healthy in the form of the financial statements expected management attention and improve the performance of the company in order to better in the following years.